2020
DOI: 10.3390/molecules25020355
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide Residues and Health Risk Assessment in Tomatoes and Lettuces from Farms of Metropolitan Region Chile

Abstract: Over the last years, the detection of pesticide residues in the official food surveillance programs of Chile has been increased, mainly in fresh vegetables such as tomatoes and lettuces. The Metropolitana Region of Chile presents the highest detections in the country. The lack of evaluations of toxicological risks in human health have increased uncertainty of the potential effects of pesticides exposures in the Chilean population. This research aims to determinate health risks assessment of pesticide residues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
28
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 34 publications
(53 reference statements)
5
28
0
1
Order By: Relevance
“…Each sample size consisted of 2 kg of fresh tomatoes wrapped in aluminium foil. The samples were processed using a grinder, and then stored in a flask and frozen at −20 °C, according to the protocol previously described elsewhere [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Each sample size consisted of 2 kg of fresh tomatoes wrapped in aluminium foil. The samples were processed using a grinder, and then stored in a flask and frozen at −20 °C, according to the protocol previously described elsewhere [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Analytical grade pesticides standards (over 99% purity) were obtained from Sigma-Aldrich (Saint Louis, MO, USA), HPLC (Cunnersdorf, Deutschland), and Chem Service (West Chester, PA, USA). Solvents and chemicals were obtained from Merck (Darmstadt, Germany) [ 22 ]. QuEChERS extraction systems were purchased from UCT (Bristol, PA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…De Silva et al (2010) add that these pesticides are also toxic to pollinators such as bees and have been associated with reduced bee populations. Statistics on residual levels of mancozeb in Kenya are still limited but grey studies from elsewhere such as Chile (Elgueta et al, 2020) and Uganda (Atuhaire et al, 2017;Kaye et al, 2015) have shown residue levels to be as much as seven times the prescribed levels. Sadly, mancozeb is a known carcinogen in rats and can cause Parkinsons' disease in humans (Ibid).…”
Section: Effects Of Misuse Of Agrochemicalsmentioning
confidence: 99%
“…This is not to say that residues are never detected in these vegetables. Elgueta et al [ 22 ] and Skovgaard et al [ 23 ] detected pesticide residues in 50% of lettuce samples with 16–20% of samples above the MRL. Santareli et al [ 24 ] also detected many lettuce samples over the MRL in Italy.…”
Section: Introductionmentioning
confidence: 99%